If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + (-7) = -25 3x + -7 = -25 Reorder the terms: -7 + 3x = -25 Solving -7 + 3x = -25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 3x = -25 + 7 Combine like terms: -7 + 7 = 0 0 + 3x = -25 + 7 3x = -25 + 7 Combine like terms: -25 + 7 = -18 3x = -18 Divide each side by '3'. x = -6 Simplifying x = -6
| 8y-32=-8(y+6) | | 25x^2-45x+8= | | 5x^2-36x+36= | | 35-19=2(x-8) | | graphy=-2x-4 | | 3x^2/5=27 | | 4k^2-9= | | 1.2y=3+y+1 | | 3y=8+y+1 | | 10x^2-41x-45= | | -9x=6 | | 2v+7-5v=-17 | | 7=-3+9 | | 3y=y+3+1 | | .03(x+40)+12.8=.4(10-x)+96 | | (3x-5)(-5)= | | 27x^2-246x-240= | | 6(5-x)-3(x-4)=6 | | p^2+p-20=0 | | 46-11=5(x-8) | | 6x^2-x+3=0 | | 4x^2-10x+25=49 | | 64-6x=12x+16 | | 10x^2-80x= | | 12-8x=111-29 | | 8w^3-3w+1=0 | | 4(2-3x)-30=10-2(x-4) | | 27x-30x=7-10 | | 9/x=15/35 | | 4v-16=48 | | 14x^2+26x-48= | | 4x^2+27+35=0 |